EFEKTIVITAS PERAWATAN ULKUS DIABETIKUM TERHADAP PENERIMAAN DIRI PASIEN DIABETES MELITUS TIPE II DI ASRI WOUND CARE CENTRE MEDAN - Elis Anggeria; Patimah Sari Siregar (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2019)
Diabetes mellitus (DM) is a group of metabolic diseases characterized by high levels of glucose in the blood (hyperglycemia) that occurs due to impaired insulin secretion, decreased insulin action, or a result of both. Self-acceptance is the ability and desire of individuals to live with all the characteristics themselves against diabetes mellitus. This study aims to determine the effectiveness of diabetic ulcer treatment on self-acceptance of Type II Diabetes Mellitus patients at Asri Wound Care Center Medan. This study uses quantitative research methods with a quasi-experimental design through the one-group pretest-posttest design approach. The population in the study as many as 20 people, with sampling techniques using saturated sampling, the research sample amounted to 20 people. This study uses a nonparametric statistical test that is paired t-test. The results of research on self-acceptance of patients with type II diabetes mellitus before treatment of diabetic ulcers showed that the majority of self-acceptance was not good, and the self-acceptance of patients after treatment of diabetic ulcers obtained the majority of good self-acceptance. The effectiveness of diabetic ulcer treatment on self-acceptance of type II diabetes mellitus patients obtained significance value p-value = 0.00 (p-value <0.05) then H0 was rejected. This means that there are differences in self-acceptance of type II Diabetes mellitus patients before and after diabetic ulcer treatment at Asri Wound Care Center Medan. Future researchers are expected to discuss more deeply about the factors that affect the self-acceptance of diabetes mellitus patients who are undergoing treatment for diabetic ulcers.